Mindfulness in the context of a romantic relationship to predict relationship satisfaction - Khorasani, Ehsan; Farrokhi, Hossein; Shoja, Elahe; Moghaddam, Mahyar; Ali Kimiaei, Seyed (International Journal of Psychosocial Rehabilitation, 2021)
Mindfulness appears to be one of the important predictors of relationship satisfaction. The degree of mindfulness displayed by a partner when involved in romantic relationship is known as relationship mindfulness. When it comes to the romantic relationship, researchers need to look at the specific type of mindfulness designed for the field of romantic relationships. Therefore, the present study seeks to show whether relationship mindfulness can predict relationship satisfaction directly. Moreover, there is a difference in mindfulness between males and females in the romantic relationship and how the relationship mindfulness can predict relationship satisfaction in this situation. In the present study, a multistage cluster sampling method was adopted to select participants from among the study population (n=386 individual). Structural equation modeling (SEM) and MANOVA was used for data analysis. Based on the results of the present study, relationship mindfulness predicted relationship satisfaction directly and significantly (p < 0.05). Further, the level of mindfulness in romantic relationship was higher for females in the present study. In addition, gratitude has been shown to be an appropriate mediator for the association between relationship mindfulness and relationship satisfaction